The Role of Social Media in Building Netizen Political Awareness in the Prabowo-Gibran Administration Era: A Netnographic Study of the Instagram Account @generasimelekpolitik - Maria Mariska Desita; Muhammad Prakoso Aji (Journal of Governance and Social Policy, 2026)
This study aims to analyze the role and visual communication strategies of the Instagram account @generasimelekpolitik in fostering the political consciousness of netizens, particularly the younger generation, during the early phase of the Prabowo Subianto–Gibran Rakabuming Raka administration. A qualitative approach with a netnographic research design was utilized to explore digital interactions naturally. Primary data collection was conducted through structured, in-depth interviews with the account managers, political communication experts, and active followers. Secondary data were gathered through digital activity data scraping to map the audience's total interaction. The research findings indicate that netizens' political consciousness is shaped through three main aspects: input consciousness, characterized by increased attention to legal issues, state apparatuses, and government oversight; output consciousness, visible in netizens' ability to comprehend and evaluate public policies; and the process of receiving information and expressing political opinions courageously within the digital space.